Implementasi Video Pembelajaran Untuk Meningkatkan Hasil Belajar Siswa pada Materi Voli di Sekolah Dasar Kelas IV SD Negeri 106790 Sei Mencirim - Ari Mecky Prawira Ketaren; M.Fadlin Al Farhans (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2025)
This study aims to determine the effectiveness of using educational videos in improving student learning outcomes in volleyball in grade IV at SD Negeri 106790 Sei Mencirim. This study uses a qualitative descriptive method with a case study approach. Data were collected through pre-tests and post-tests to measure improvements in student understanding and skills, as well as interviews with students and teachers to explore their perceptions of the use of educational videos. The results showed that there was a significant increase in student learning outcomes after the use of educational videos. The average student score on the theory test increased from 55% to 75%, and their technical skills also improved, especially in terms of serving, passing, and smashing. Interviews with students and teachers revealed that educational videos made it easier to understand volleyball techniques, increased student engagement, and made learning more interesting. Based on these results, it can be concluded that instructional videos are effective in improving student learning outcomes in volleyball in grade IV at SD Negeri 106790 Sei Mencirim.